The Information Systems Academic Discipline in Australia - G. Gable, Guy; Gregor, Shirley; Clarke, Roger; Ridley, Gail; Smyth, Robert (ANU Press, 2008)
This book represents the second phase of a multi-method, multi-study of the 'Information Systems Academic Discipline in Australia'. Drawing on Whitley's Theory of Scientific Change, the study analysed the degree of 'professionalisation' of the Information Systems Discipline, the overarching research question being 'To what extent is Information Systems a distinct and mature discipline in Australia?' The book chapters are structured around three main sections: a) the context of the study; b) the state case studies; and c) Australia-wide evidence and analysis. The book is crafted to be accessible to IS and non-IS types both within and outside of Australia. It represents a 'check point'; a snapshot at a point in time. As the first in a hoped for series of such snap-shots, it includes a brief history of IS in Australia, bringing us up to the time of this report. The editorial team comprises Guy Gable, architect and leader; Bob Smyth, project manager; Shirley Gregor, sponsor, host and co-theoretician; Roger Clarke, discipline memory; and Gail Ridley, theoretician. In phase two, the editors undertook to examine each component study, with a view to arriving at an Australia-wide perspective.